ANALYSIS OF AGRICULTURAL SOIL CONDITIONS 20 YEARS POST-TSUNAMI USING RESISTIVITY AND SOIL PH METHODS - Adiannur, Rahiel; Amsir, Amsir; Masrurah, Zakia; Marwan, Marwan; Mohammed, Mustapha Adejo (Indonesian Physical Review, 2025)
The tsunami that struck Aceh in 2004 caused significant damage to agricultural land, altering soil properties and affecting productivity. Mon Ikeun Village was one of the most affected areas in the Lhoknga Subdistrict of Aceh Besar Regency. As an agricultural area vulnerable to soil salinization, it faced reduced soil quality, fertility, and nutrient availability risks, which could significantly decrease crop productivity. Therefore, assessing the current condition of agricultural soils is essential to determine whether recovery has occurred or if contamination persists. This research investigates the condition of agricultural soils two decades after the tsunami by analyzing resistivity and soil pH measurements. The resistivity data were collected using a SuperSting R8 device with a Wenner configuration and subsequently processed with IPI2WIN. The pH was determined with a Hanna HI 991001 pH Meter. The results reveal that the affected soils present resistivity values between 9.06 Ωm and 131 Ωm, indicating compositions of sandy clay and sand layers. Soil pH ranges from 4.9 to 6.2, indicating slightly acidic to near-neutral conditions, suitable for agriculture. These results indicate a substantial recovery in soil conditions, especially when compared to a control site in a non-affected area with similar land characteristics. This reinforces the interpretation that the tsunami’s impact has diminished over time. This recovery is likely influenced by natural processes such as leaching of contaminants through rainfall. This integrated approach effectively evaluates long-term changes in agricultural soil affected by the tsunami. However, to obtain a clearer understanding of the soil recovery process, future studies could include additional measurements such as soil nutrient analysis, electrical conductivity, or salinity levels to offer more detailed insights.